Occurrence of the" Peaking Effect" Corresponding to the" Highest Range of Effective Intensities" exhibited by Bacteriorhodopsin (bR)-Carboxymethylcellulose (CMC) Biosensor upon Illumination - Vengadesh, P.; Abd Majid, Wan Haliza; Anandan Shanmugam, S.; Low, K.S. (Faculty of Science, University of Malaya, 2008)
Photo-electrical characterization works were carried out to understand the basic functionality of the novel bacteriorhodopsin (bR) - Carboxymethylcellulose (CMC) photosensor proposed and fabricated earlier. A single-pixel sensor was fabricated and its photoresponse towards light intensities and thermal variations studied. The occurrence of the "peaking effect" corresponding to a certain "highest range of effective intensities" upon light illumination was also observed and discussed.